The Women - Hannah, Kristin (New York, 2024)
Women can be heroes. When twenty-year-old nursing student Frances "Frankie" McGrath hears these unexpected words, it is a revelation. Raised on idyllic Coronado Island and sheltered by her conservative parents, she has always prided herself on doing the right thing, being a good girl. But in 1965 the world is changing, and she suddenly imagines a different choice for her life. When her brother ships out to serve in Vietnam, she impulsively joins the Army Nurse Corps and follows his path. As green and inexperienced as the men sent to Vietnam to fight, Frankie is overwhelmed by the chaos and destruction of war, as well as the unexpected trauma of coming home to a changed and politically divided America.
Keywords: United States; Army Nurse Corps; Fiction; Fiction; Fiction; Veterans; Young women; Fiction; Women; Psychic trauma; Vietnam War, 1961-1975; Nurses; Vietnam War, 1961-1975; Fiction; Women in war; Fiction; Fiction; Fiction; United States; Armed Forces; Nurses; Fiction; United States; Social conditions; 1945-; Fiction; War fiction; Psychological fiction; Historical fiction